Development of project-based learning using mathematical aquaponics with a deep learning approach - Fury Styo Siskawati; Sholahudin Al Ayubi; A. Mujib MT; Endang Sri Wahyuni; Maswar Maswar (Fakultas Tarbiyah Universitas Ibrahimy, 2026)
This study developed a mathematics learning medium based on aquaponics (Mathematic Aquaponik) to support Project-Based Learning (PjBL) with a deep learning approach in a Mathematical Modelling course. The study was motivated by low mathematical literacy and problem-solving skills among Indonesian students, particularly at higher cognitive levels, highlighting the need for contextual and authentic learning media. Research and development (R&D) using the ADDIE model-analysis, design, development, implementation, and evaluation was employed. Validity was assessed by content and media experts. At the same time, practicality and effectiveness were tested through a limited trial of six students and a field trial using a one-group pretest–posttest design. Results indicate that the media is valid, practical, and effective in enhancing conceptual understanding, problem-solving, higher-order thinking skills, and deep learning behaviours (pretest 48.60 → posttest 76.20; N-gain 0.53). Mathematic Aquaponik provides authentic, contextual learning experiences that foster HOTS and 21st-century competencies aligned with the Kurikulum Merdeka and Profil Pelajar Pancasila.